2013
DOI: 10.3747/co.20.1546
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Subacute Cutaneous Lupus Erythematosus Associated with Nab-Paclitaxel Therapy

Abstract: by fluorescence in situ hybridization. Computed tomography imaging revealed lesions in keeping with small-volume lung and liver metastases and bilateral ovarian metastases.The patient was therefore started on first-line systemic therapy for metastatic breast cancer, using nanoparticle albumin bound (nab)-paclitaxel 260 mg/m 2 intravenously every 21 days. She initially tolerated the nab-paclitaxel well, with toxicities limited to alopecia and mild fatigue. After the third infusion, she developed a new skin erup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 18 publications
0
14
0
1
Order By: Relevance
“…The incidence of rash is comparable to that observed with the solvent-based paclitaxel (overall incidence of 4%), except in Asian populations where it appeared to affect more than a third of patients in some series [158, 160]. Nab-paclitaxel-induced SCLE is similar in all aspects to that observed with paclitaxel ( see above ) [54]. Photosensitivity reaction can also occur [161].…”
Section: Nab-paclitaxelmentioning
confidence: 66%
See 1 more Smart Citation
“…The incidence of rash is comparable to that observed with the solvent-based paclitaxel (overall incidence of 4%), except in Asian populations where it appeared to affect more than a third of patients in some series [158, 160]. Nab-paclitaxel-induced SCLE is similar in all aspects to that observed with paclitaxel ( see above ) [54]. Photosensitivity reaction can also occur [161].…”
Section: Nab-paclitaxelmentioning
confidence: 66%
“…SCLE has also been reported with nab-paclitaxel, portraying the same clinical, histological or laboratory abnormalities [54]. …”
Section: Cutaneous Toxicitiesmentioning
confidence: 99%
“…12,13 Gallo et al 14 reported three cases of eccrine squamous syringometaplasia secondary to docetaxel related to extravasation of the drug during the infusion and revised other similar cases, [15][16][17][18][19][20][21] concluding that it could be a frequent, but unreported histopathologic finding. Taxane-associated photosensitivity has been reported as photo recall phenomenon, [22][23][24][25] photo-onycholysis, erythema multiforme and onycholysis 23 and subacute cutaneous lupus erythematosus, [26][27][28][29][30][31][32][33] associated or not to systemic lupus erythematosous. 28,31 The photo recall phenomenon is characterized by a drug-induced skin rash located on a previously sunburned area that occurs between 1 and 8 days after the sunburn and between 1 day and 1 week after drug administration.…”
Section: Discussionmentioning
confidence: 99%
“…More rarely, life‐threatening cutaneous eruptions, including erythema multiforme, Stevens‐Johnson syndrome and toxic epidermal necrolysis may occur in association with systemic taxane administration . Other cutaneous manifestations include erythrodysesthesias, drug‐induced lupus erythematosus, photosensitivity reactions and scleroderma‐like changes . However, despite the immense literature documenting the various toxicities of systemic taxane administration, systemic toxicities resulting from topical therapy, such as intravesical therapy, have not been reported.…”
Section: Discussionmentioning
confidence: 99%